Cultivating dental excellence: advancing dental education in Malaysian higher institutions - Sim, Galvin Siang Lin; Muhamad Halil, Mohd Haikal (Opinion Advance, 2024)
Malaysia is no exception (Komabayashi et al., 2007). In this context, dental education refers to the academic and practical training provided to individuals pursuing careers in dentistry. It encompasses the curriculum content, teaching methods, assessments, faculty development, and infrastructure within higher educational institutions that prepare students for professional practice as a qualified dentist. Much like in other countries, there is a growing need to emphasise the significance of Malaysian dental education in advancing the healthcare system. For instance, a well-designed dental curriculum equips future dental practitioners with the skills and knowledge needed to address the diverse oral health needs of the population, thereby enhancing the effectiveness and treatment modalities of oral healthcare services (Mays, 2021).